Belief revision meets philosophy of science - Olsson, Erik J.; Enqvist, Sebastian (Logic, epistemology, and the unity of science, 2011)
Belief revision theory and philosophy of science both aspire to shed light on the dynamics of knowledge? on how our view of the world changes (typically) in the light of new evidence. Yet these two areas of research have long seemed strangely detached from each other, as witnessed by the small number of cross-references and researchers working in both domains. One may speculate as to what has brought about this surprising, and perhaps unfortunate, state of affairs. One factor may be that while belief revision theory has traditionally been pursued in a bottom- up manner, focusing on the endeavors of single inquirers, philosophers of science, inspired by logical empiricism, have tended to be more interested in science as a multi-agent or agent-independent phenomenon.